2017
DOI: 10.3847/1538-4357/aa7b30
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation Modified by DIG and Dust as Seen in M31

Abstract: The spatial distribution of dust in galaxies affects the global attenuation, and hence inferred properties, of galaxies. We trace the spatial distribution of dust in five fields (at 0.6-0.9 kpc scale) of M31 by comparing optical attenuation with the total dust mass distribution. We measure the attenuation from the Balmer decrement using Integral Field Spectroscopy and the dust mass from Herschel far-IR observations. Our results show that M31's dust attenuation closely follows a foreground screen model, contrar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 111 publications
(191 reference statements)
4
15
0
Order By: Relevance
“…However, this prescription may differ given the small spatial scales probed in M31 (Faesi et al 2014). In our previous paper, Tomičić et al (2017), we found that the dust/gas distribution in M31 mostly follows the foreground screen models, and that the dust scale height is larger than the scale height of the DIG and HII regions for our studied fields. Therefore, in the following calculation, we will also assume a simple screen model of the dust/gas distribution, use the CCM extinction curve, the Balmer decrement of Hα/Hβ=2.86, and the selective extinction with R V =3.1 (Kreckel et al 2013, Tomičić et al 2017).…”
Section: Conversion From Hα and Fuv To Sfrsupporting
confidence: 53%
See 3 more Smart Citations
“…However, this prescription may differ given the small spatial scales probed in M31 (Faesi et al 2014). In our previous paper, Tomičić et al (2017), we found that the dust/gas distribution in M31 mostly follows the foreground screen models, and that the dust scale height is larger than the scale height of the DIG and HII regions for our studied fields. Therefore, in the following calculation, we will also assume a simple screen model of the dust/gas distribution, use the CCM extinction curve, the Balmer decrement of Hα/Hβ=2.86, and the selective extinction with R V =3.1 (Kreckel et al 2013, Tomičić et al 2017).…”
Section: Conversion From Hα and Fuv To Sfrsupporting
confidence: 53%
“…M31 is a highly inclined galaxy, and the fields used in this paper probe galactocentric radii that are larger than the galaxies (KINGFISH, SINGS and CALIFA surveys, and NGC 3627, NGC 628) used for calibration of the SFR prescriptions in the literature. This leads to higher attenuation for the same dust mass surface density compared to nearby galaxies (Tomičić et al 2017), and larger a IR and b IR factors. Due to the large galactocentric distance, the M31 field also have a low surface brightness in the mid-IR and observed Halpha emission (Fig.…”
Section: Galactocentric Radius and Inclinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The trend is largely driven by the physical characteristics of the ISM such as gas-phase metallicity and ionization parameter which may vary across a galaxy (e.g. Tomičić et al 2017).…”
Section: Extinction Correctionmentioning
confidence: 99%